928-P: The Use of a Novel CGM-Informed Insulin Bolus Calculator Mobile Application by People with Type 1 and Type 2 Diabetes Improves Time in Range - SHOMALI, MANSUR; KELLY, COLLEEN; IYER, ANAND K.; PARK, JEAN Y.; ALEPPO, GRAZIA (Diabetes (New York, N.Y.), 2023)
Background and Aims: People with diabetes on basal-bolus insulin regimens face challenges calculating bolus doses. Continuous glucose monitoring (CGM) systems can assist users with bolus dosing optimization through trend arrows. The purpose of this study was to demonstrate the safety and effectiveness of a CGM-informed insulin bolus calculator (IBC, Welldoc, Inc., Columbia, MD, U.S.A.) integrated into a mobile application that applies trend arrow and exercise adjustments to the bolus insulin dose recommendation. This investigational software also provided real-time coaching on CGM data to assist users in improving their time in range (TIR). Methods: Fifty-four participants with diabetes using CGM (Dexcom G6, San Diego, CA, U.S.A.) were enrolled in a 30-day prospective study conducted at two research sites. Participants were asked to use the mobile application to monitor their CGM data and calculate their insulin doses. TIR during the prospective 30-day period was compared to that from 30 days of baseline data. Three populations were defined: 1) the intention-to-treat (ITT) group consisted of all enrolled subjects; 2) the complete cases (CC) group had ≥90% sensor wear time; and 3) the per-protocol (PP) group used the IBC at least 30 times during the study period. Results: In the ITT group, the TIR improved from 68.4% to 71.8% (N=54, P=0.013). In the CC group, the TIR improved from 69.1% to 73.0% (N=49, P=0.005). In the PP group, the TIR improved from 69.2% to 73.0% (N=39, P=0.017). There was no increase in time with low glucose (<70 mg/dL) in all three populations. In a subgroup analysis, TIR increased from 74.7% to 81.4% in those with type 2 diabetes and from 64.4% to 65.2% in those with type 1 diabetes. Conclusions: Use of a novel CGM-informed insulin bolus calculator with trend arrow and exercise dose adjustment by individuals with type 1 and type 2 diabetes was associated with significant improvement in TIR.